Europäische Einigungsbestrebungen vom Mittelalter bis zur Gründung der Europäischen Wirtschaftsgemeinschaft (EWG) 1957 - Majer, DiemutHöhne, Wolfgang (Juris Fontes : Rechtsquellen in Vergangenheit und Gegenwart / Hrsg. von D. Majer, W. Hoehne, W.-D. Barz, 2014)
This volume describes Europe as a center for many crises and at the same time as a stronghold of culture - beginning with Christendom and Enlightenment up to Music, poetry and arts. This book looks at the history of the European thoughts and shows that those thoughts came to life already in the medieval ages. The Ideas of the philosophes in former centuries show surprising similarities with the actual problems of the European Union - always in connection with the desire for peace in Europe.